Multihoming in the market for payment media: evidence from young Finnish consumers - Ari Hyytinen; Tuomas Takalo (Bank of Finland, 2004)
In the market for payment media, some consumers use only one medium when paying for their point-of-sale transactions, while others multihome and use many.As this pattern reflects the diffusion of new payment media, we take a look at the determinants of the adoption of new payment media through the window of multihoming. Using data on young Finnish consumers, we find that one key determinant of multihoming behaviour is consumer awareness.Our instrumental variable estimates indicate that the better informed use 1.2-1.3 times more payment media than the less informed. Because many payment method innovations are typically first used simultaneously with established methods, our results suggest that increasing consumer awareness could significantly speed up the adoption of new means of payment, such electronic money and mobile payments.
URN:NBN:fi:bof-20140807483
Keywords: G20; E59; 330; payment media; multihoming; consumer awareness; adoption of financial technology